2007
DOI: 10.1124/jpet.107.133538
|View full text |Cite
|
Sign up to set email alerts
|

Contractile and Vasorelaxant Effects of Hydrogen Sulfide and Its Biosynthesis in the Human Internal Mammary Artery

Abstract: This study aimed to test these hypotheses: cystathionine ␥-lyase (CSE) is expressed in a human artery, it generates hydrogen sulfide (H 2 S), and H 2 S relaxes a human artery. H 2 S is produced endogenously in rat arteries from cysteine by CSE. Endogenously produced H 2 S dilates rat resistance arteries. Although CSE is expressed in rat arteries, its presence in human blood vessels has not been described. In this study, we showed that both CSE mRNA, determined by reverse transcription-polymerase chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
121
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(134 citation statements)
references
References 25 publications
10
121
0
3
Order By: Relevance
“…Mixing of H 2 S donor NaHS with NO donors (SNP or SNAP) diminished vasorelaxant effect of each NO donor on rat aorta and low concentrations of H 2 S contracted human internal mammary artery (Ali et al 2006;Webb et al 2008). It was suggested that H 2 S was able to inactivate NO by chemical reaction with NO to produce an unidentified nitrosothiol (Ali et al 2006;Whiteman et al 2006;Webb et al 2008). Munro and Williams (2000) supposed nitrosodisulfide ion ONSS -as the result of RSNOs reaction with sulfur-centred nucleophiles.…”
Section: Discussionmentioning
confidence: 99%
“…Mixing of H 2 S donor NaHS with NO donors (SNP or SNAP) diminished vasorelaxant effect of each NO donor on rat aorta and low concentrations of H 2 S contracted human internal mammary artery (Ali et al 2006;Webb et al 2008). It was suggested that H 2 S was able to inactivate NO by chemical reaction with NO to produce an unidentified nitrosothiol (Ali et al 2006;Whiteman et al 2006;Webb et al 2008). Munro and Williams (2000) supposed nitrosodisulfide ion ONSS -as the result of RSNOs reaction with sulfur-centred nucleophiles.…”
Section: Discussionmentioning
confidence: 99%
“…H 2 S is endogenously produced from L-cysteine predominantly by the enzymes cystathionine-γ-lyase (CSE) and cystathionine-β-synthase (CBS) in a variety of animals, from invertebrates to mammals (Fiorucci et al 2005b;Gainey and Greenberg 2005;Geng et al 2004b;Julian et al 2005;Julian et al 2002;Kimura 2000;Kimura et al 2005;Wang 2002;Webb et al 2008). Recently, 3-mercaptopyruvate sulfurtransferase (3-MST), in conjunction with cysteine aminotransferase, has also been found to produce H 2 S from cysteine (Shibuya et al 2009;Shibuya et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Since then a variety of physiological roles have been proposed for H 2 S (Lowicka and Beltowski 2007;Szabo 2007), and at least some capacity for H 2 S production has been demonstrated in several vertebrate tissues Olson 2005;Olson et al 2006;Zhao et al 2003), including human mammary artery (Webb et al 2008). When exogenously applied to isolated blood vessels of vertebrates, H 2 S elicits responses that range from a monophasic relaxation or contraction, to multiphasic contraction-relaxation-contraction responses, depending on the phylogenetic class and type of vessel examined (Dombkowski et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since NaHS is five-to-nine fold more potent in relaxing mesenteric arteries than thoracic aorta and pulmonary artery (EC 50 25 µM vs. 125 µM and 233 µM, respectively), it has been proposed as a key regulator of peripheral resistance arteries and, therefore, of blood pressure [15]. H 2 S has been shown to dilate other isolated mammalian blood conduits in vitro, such as human internal mammary artery [103], mouse aorta and ear microcirculation [104,105], and newborn pig cerebral arterioles [106]. Consistent with these data, the systemic injection of NaHS at 10-50 activity in VSMCs, which leads to vasorelaxation in a PKG-dependent manner [48,111,112].…”
Section: The Roles Of H 2 S and No In Vasodilationmentioning
confidence: 99%